Linkage Analysis of Schizophrenia Controlling for Population Substructure - Paunio, Tiina (2009)
Etiological heterogeneity and complexity has hampered attempts to identify predisposing genes for schizophrenia. We sought to minimize the number of segregating genes involved by focusing on a population isolate with elevated disease prevalence. We exploited the well-established population history, and searched for disease susceptibility loci in families from two alternative founder lineages. We studied 28 schizophrenia pedigrees (123 nuclear families) from an outlying municipality on the eastern border of Finland. We divided the families based on their genealogy and defined two routes of immigration: southern and northern. We examined the kinship coefficients and allele frequency distributions within each group, and performed a linkage analysis based on 497 microsatellite markers across the genome. A high degree of historical relatedness was demonstrated by higher sharing of alleles than predicted by the relationships we identified within the previous four generations alone, as would be expected. Between the two subpopulations, allele frequencies were significantly different, consistent with their isolated genealogies. The southern families showed some evidence of linkage in a schizophrenia locus at 4q23 (Z=3.3) near our previous finding with quantitative variation in verbal learning and memory [Paunio et al. (2004); Hum Mol Genet 13: 1693–1702], while the northern pedigrees gave most significant evidence on 10q21 (Z=2.53). Joint analysis of families from both lineages suggested evidence of linkage only at 3p14 (Z=3.18). Thus the detailed genealogical information led us to identification of distinct linkage signals for schizophrenia susceptibility loci between the three analyses we performed.